1973
DOI: 10.1128/jvi.11.4.527-534.1973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhibition of Macromolecule Synthesis on the Association of Bacteriophage T4 DNA with Membrane

Abstract: The "Mg2+-Sarkosyl crystals" (M band) technique distinguishes between membrane-bound and free intracellular DNA. This procedure was employed to investigate the nature of the reactions necessary to convert input T4 DNA to a rapidly sedimenting form. Energy poisoning inhibits this attachment reaction. Neither protein nor DNA synthesis appears to be required, but experiments with rifampin and extensively irradiated T4 suggest that RNA synthesis is involved. These results were confirmed by a second procedure for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, if the controlled, sequential synthesis of enzymes observed in vivo could be demonstrated in vitro by use of antibiotics such as rifampin or chloramphenicol, an approach might be possible to providing substantial information about the meaning of polarity in gene transcription. We have particularly in mind the formation of transcription complexes (1,3,23) and the relationship of transcription to the association of T4 DNA with bacterial membranes (8).…”
Section: Discussionmentioning
confidence: 99%
“…However, if the controlled, sequential synthesis of enzymes observed in vivo could be demonstrated in vitro by use of antibiotics such as rifampin or chloramphenicol, an approach might be possible to providing substantial information about the meaning of polarity in gene transcription. We have particularly in mind the formation of transcription complexes (1,3,23) and the relationship of transcription to the association of T4 DNA with bacterial membranes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Control of the phage DNA replication requires that the nucleoid attaches to the cell membrane [13,25,28]. Through the interaction with RNA polymerase, rifampicin has been demonstrated to influence the structure of the bacterial nucleoid [4, 14,32]. Doworsky and Schaechter [12] have shown that binding of rifampicin to bacterial RNA polymerase can reduce the attachments of nucleoid to cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, using polyacrylamide gel electrophoresis techniques, Horvitz (28) failed to detect any early protein whose synthesis was controlled by the injected protein. (ii) Parental T4 DNA rapidly attaches to the plasma membrane, and this attachment is not contingent upon prior synthesis of phagecoded proteins (22). Associations between parental phage DNA and the plasma membrane have been implicated in transcriptional control (17).…”
Section: Discussionmentioning
confidence: 99%
“…Associations between parental phage DNA and the plasma membrane have been implicated in transcriptional control (17). Mathews (38) has shown that DHFR is overproduced in cells infected with UV-irradiated T2 phage, and UV-induced damage is known to inhibit normal attachment of parental phage DNA to the cellular membrane (22).…”
Section: Discussionmentioning
confidence: 99%